Sneathia amnii and Maternal Chorioamnionitis and Stillbirth, Mozambique - Pio Vitorino; Rosauro Varo; Paola Castillo; Juan Carlos Hurtado; Fabiola Fernandes; Ana Marta Valente; Rita Mabunda; Sibone Mocumbi; Joy M. Gary; Tiffany G. Jenkinson; Inacio Mandomando; Dianna M. Blau; et al. (Emerging Infectious Diseases, 2019)
We report a case of Sneathia amnii as the causative agent of maternal chorioamnionitis and congenital pneumonia resulting in a late fetal death in Mozambique, with strong supportive postmortem molecular and histopathologic confirmation. This rare, fastidious gram-negative coccobacillus has been reported to infrequently cause abortions, stillbirths, and neonatal infections.